Educational Supervision as a Strategic Mechanism for Improving Instructional Quality - Intan Nurhasanah; Eva Dianawati Wasliman (Journal of Educational Management Research, 2026)
This study aims to examine the implementation of educational supervision based on Edward Deming’s Total Quality Management (TQM) principles in improving learning quality. A qualitative research design was employed, utilizing interviews, observations, and document analysis to capture supervisory practices. Data were analyzed using the Plan–Do–Check–Act (PDCA) cycle as a framework for supervision quality management. The findings reveal that educational supervision is implemented systematically through structured planning, professional execution, evidence-based evaluation, and continuous follow-up. The Check and Act stages play a critical role in strengthening teacher professionalism, fostering reflective practices, and sustaining a culture of quality improvement. These stages enable supervisors to use evaluative data as a basis for corrective actions and continuous development. The study implies that integrating TQM principles into educational supervision can transform supervision from a predominantly administrative function into a strategic mechanism for enhancing instructional quality. This research contributes both conceptually and practically to the development of supervision quality management in secondary education.